Clinical and biological impact of the exposome on the skin - Passeron, T.; Krutmann, J.; Andersen, M.L.; Katta, R.; Zouboulis, C.C. (Journal of the European Academy of Dermatology and Venereology, 2020)
The skin exposome is defined as the totality of environmental exposures over the life course that can induce or modify various skin conditions. Here, we review the impact on the skin of solar exposure, air pollution, hormones, nutrition and psychological factors. Photoageing, photocarcinogenesis and pigmentary changes are well‐established consequences of chronic exposure of the skin to solar radiation. Exposure to traffic‐related air pollution contributes to skin ageing. Particulate matter and nitrogen dioxide cause skin pigmentation/lentigines, while ozone causes wrinkles and has an impact on atopic eczema. Human skin is a major target of hormones, and they exhibit a wide range of biological activities on the skin. Hormones decline with advancing age influencing skin ageing. Nutrition has an impact on numerous biochemical processes, including oxidation, inflammation and glycation, which may result in clinical effects, including modification of the course of skin ageing and photoageing. Stress and lack of sleep are known to contribute to a pro‐inflammatory state, which, in turn, affects the integrity of extracellular matrix proteins, in particular collagen. Hormone dysregulation, malnutrition and stress may contribute to inflammatory skin disorders, such as atopic dermatitis, psoriasis, acne and rosacea.